2006
DOI: 10.1109/jsac.2005.864018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frequency offsets and IQ imbalance on MC-CDMA reception based on channel tracking

Abstract: New air interfaces are currently being developed to meet the high spectral efficiency requirements of the emerging wireless communication systems. Multi-carrier code-division multiple access (MC-CDMA) is seen as a promising candidate for the fourth generation (4G) cellular communication systems because it can interestingly deal with the multipath propagation at a low processing complexity. Besides spectral efficiency and power consumption, the production cost of the transceiver should also be optimized. Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…According to Eqs. (8), (9) and (12), Fig. 6 is the architecture of the crossvalidation estimator, and Fig.…”
Section: Mimo-ofdm Modemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. (8), (9) and (12), Fig. 6 is the architecture of the crossvalidation estimator, and Fig.…”
Section: Mimo-ofdm Modemmentioning
confidence: 99%
“…Therefore, introducing the filter mismatch phenomenon into the system increases the estimation error. The I/Q imbalance with filter mismatch, namely frequency-dependent I/Q imbalance, is much critical for OFDM direct-conversion receivers to make the corresponding estimation and compensation be extremely difficult [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the carrier frequency offset (CFO), caused by the local oscillators at the transmitter and receiver, and the IQ imbalance, caused by the use of direct-conversion analog front-ends, are destructive [4]. It has been recently shown that those effects can be advantageously compensated digitally [5].…”
Section: Introductionmentioning
confidence: 99%
“…The time impulse response mismatch, mostly caused by a mismatch between the two LPFs, causes a frequency dependent I/Q imbalance which must be estimated and compensated per carrier. The impact of I/Q imbalance on OFDM and CDMA is shown to be critical in [1] and [2]. Even though the degradation created by the LO imbalance is a dominant effect, the frequency dependent part gives enough degradation to make the use of high modulation schemes impossible.…”
Section: Introductionmentioning
confidence: 99%